2013
DOI: 10.20996/1819-6446-2013-9-1-15-24
|View full text |Cite
|
Sign up to set email alerts
|

Factors Effecting the Decompensation of Chronic Heart Failure in the Elderly

Abstract: Aim. To identify risk factors of decompensation of chronic heart failure (CHF) and related hospitalization in elderly outpatients. Material and methods. The total of 248 patients aged 60-85 years with CHF NYHA class II-IV were enrolled into the study. The first group consisted of 87 (35.1%) patients who required hospitalization due to CHF decompensation during the follow-up, the second group -of 161 patients without need for hospital admission. All the patients had undergone clinical and laboratory examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Of the 12 studies, 1 reported their data as both categorical and continuous variables, 8 reported data as categorical variables, and 3 reported data as continuous variables. Pooled data from nine studies reporting the estimates as categorical variables showed that hyperuricaemia was associated with an increased risk of the composite of death or cardiac events in HF patients (HR 1.39, 95% CI 1.18–1.63) but substantial statistical heterogeneity was found (I 2 = 66.3%) ( Figure C ) . Although every 1 mg/dL increase in serum uric acid was associated with a 28% increase in the risk of the composite endpoint from pooling the four studies reporting the estimates as continuous variables, the calculation of risk did not reach statistical significance (HR 1.28, 95% CI 0.97–1.70) .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Of the 12 studies, 1 reported their data as both categorical and continuous variables, 8 reported data as categorical variables, and 3 reported data as continuous variables. Pooled data from nine studies reporting the estimates as categorical variables showed that hyperuricaemia was associated with an increased risk of the composite of death or cardiac events in HF patients (HR 1.39, 95% CI 1.18–1.63) but substantial statistical heterogeneity was found (I 2 = 66.3%) ( Figure C ) . Although every 1 mg/dL increase in serum uric acid was associated with a 28% increase in the risk of the composite endpoint from pooling the four studies reporting the estimates as continuous variables, the calculation of risk did not reach statistical significance (HR 1.28, 95% CI 0.97–1.70) .…”
Section: Resultsmentioning
confidence: 97%
“…In total, 33 studies were retrieved after a detailed review of 1745 citations. Among these, 5 studies reported on the incidence of HF, and 28 studies reported on the adverse outcomes of HF patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we did not include those studies in our analysis. Finally, there were 74 studies 27–100 and 38 studies 85,101–137 in which we could estimate RRs for new‐onset and recurrent HF, respectively, in relation to DM. One study 85 examined both new‐onset and recurrent HF risk.…”
Section: Resultsmentioning
confidence: 99%